Microwave‐assisted synthesis and antituberculosis screening of Some 4‐((3‐(trifluoromethyl)‐5,6‐dihydro‐[1,2,4]triazolo[4,3‐a]pyrazin‐7(8H)‐l)methyl)benzenamine hybrids - Patil, Y.; Shingare, R.; Choudhari, A.; Sarkar, D.; Madje, B. (Journal of Heterocyclic Chemistry, 2019)
In the present investigation, a series of 4‐((3‐(trifluoromethyl)‐5,6‐dihydro‐[1,2,4]triazolo[4,3‐a]pyrazin‐7(8H)‐yl)methyl)benzenamine analogs 6a–o were synthesized and characterized by IR, NMR (1H and 13C), and mass spectra. All newly synthesized compounds 6a–o were prepared under conventional and microwave irradiation methods. These compounds obtained in higher yields and in shorter reaction times in the microwave irradiation method when compared with the conventional method. Synthesized compounds 6a–o were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra using an established XTT reduction menadione assay. Among the screened compounds, 6i (IC50: 1.82 μg/mL), 6j (IC50: 1.02 μg/mL), and 6k (IC50: 1.59 μg/mL) showed excellent activity. Furthermore, compound 6i showed MIC90 value of 16.02 μg/mL. In summary, the results indicate the identification of some novel, selective, and specific inhibitors against M. tuberculosis that can be explored further for the potential antitubercular drug.